Could advanced drug delivery systems be the future in cardiovascular revascularization medicine?. (August 2017) - Zuin, Marco; Rigatelli, Gianluca; Faggian, Giuseppe; L'Erario, Roberto; Chinaglia, Mauro; Roncon, Loris
Acute myocardial infarction, stroke and pulmonary embolism required a prompt revascularization to restore the normal blood flow as soon as possible. Fibrinolytic treatment has gradually become both dated and underused in the treatment of acute myocardial infarction, after the wide diffusion of cathlab and percutaneous transluminal coronary angioplasty. Conversely, the use of systemic thrombolysis remained a benchmark in the treatment of both ischemic stroke and massive pulmonary embolism. In daily clinical practice, the use of thrombolytic agents is often limited by absolute and/or relative contraindications and possible adverse events after the drug administration, as intracranial and/or extracranial bleeding events. To minimize these problems, during the last years, the introduction of nanotechnology in the field of cardiovascular revascularization medicine has created several fascinating results. In the present article, we describe these recent findings and their possible implications in future clinical practice.